Studi Kasus Stunting pada Anak TBC Usia 36 Bulan di Wilayah Kerja Puskesmas Mangkang Kota Semarang Tahun 2024 - Luluk Nur Fadhillah Mukminurrahmah; Lauren Cahayarsi; Latifatun Nisa; Nella Vallen; Saedatun Saedatun (Jurnal Medika Nusantara, 2025)
Stunting remains a major public health issue in Indonesia, including in Semarang City. Stunting can be exacerbated by infectious diseases such as tuberculosis (TB), which hinder nutrient absorption and child growth. This study aims to evaluate risk factors and the effectiveness of interventions in managing stunting in children with TB infection in the working area of Puskesmas Mangkang. This research employs a case study design with an observational approach. Data were collected through home visits, child growth monitoring, and collaboration with healthcare professionals in providing interventions such as Supplementary Feeding (PMT) and milk. The results of this research is A 36-month-old child with stunting and TB infection showed an increase in weight and height after receiving interventions for eight weeks. However, the increase was not significant. Risk factors contributing to stunting in this case included a history of Low Birth Weight (LBW), poor dietary habits, and ongoing TB infection treatment. Conclusion: Managing stunting in children with TB infection should be conducted gradually, with a primary focus on treating the infection before optimizing nutritional status. A multidisciplinary approach, including nutritional therapy, regular monitoring, and family education, is essential for more effective results.